Cryopreservation of Arachis Pintoi (leguminosae) Somatic Embryos - Rey, Hebe Yolanda; Faloci, Mirta Mabel; Medina, Ricardo Daniel; Dolce, Natalia Raquel; Engelmann, Florent; Mroginski, Luis Amado (CryoLetters, 2013)
In this study, we successfully cryopreserved cotyledonary somatic embryos of diploid and triploid Arachis pintoi cytotypes using the encapsulation-dehydration technique. The highest survival rates were obtained when somatic embryos were encapsulated in calcium alginate beads and precultured in agitated (80 rpm) liquid establishment medium (EM) with daily increasing sucrose concentration (0.50, 0.75, and 1.0 M). The encapsulated somatic embryos were then dehydrated with silica gel for 5 h to 20% moisture content (fresh weight basis) and cooled either rapidly (direct immersion in liquid nitrogen, LN) or slowly (1ºC min-1 from 25ºC to -30ºC followed by immersion in LN). Beads were kept in LN for a minimum of 1 h and then were rapidly rewarmed in a 30ºC water-bath for 2 min. Finally, encapsulated somatic embryos were post-cultured in agitated (80 rpm) liquid EM with daily decreasing sucrose concentration (0.75 and 0.5 M) and transferred to solidified EM. Using this protocol, we obtained 26% and 30% plant regeneration from cryopreserved somatic embryos of diploid and triploid cytotypes. No morphological abnormalities were observed in any of the plants regenerated from cryopreserved embryos and their genetic stability was confirmed with 10 isozyme systems and nine RAPD profiles.
Keywords: Somatic embryo; Cryopreservation; Encapsulation-dehydration; Genetic stability